Foot care practice and associated factors among patients with lymphoedema in Boreda district, Gamo zone, southern Ethiopia, 2020. Implications for elimination of podoconiosis and lymphatic filariasis - Chuchu Churko; Tsegaye Yohanes; Alemayehu Bekele Kassahun; Nathan Desalegn; Gesila Endashaw; Mekuria Asnakew Asfaw (Journal of Foot and Ankle Research, 2021)
Abstract Background Lymphatic filariasis is ranked as the second leading cause of disability world‐wide. The current global programme to eliminate lymphatic filariasis is based on the interruption of transmission and the alleviation of disability and suffering. Objective to assess foot care practice and associated factors among lymphoedema patients in Boreda district, Gamo zone Southern Ethiopia. Methods a community based cross sectional study was employed from December 2020 to June 2021 in Boreda district. Simple random sampling technique was used for selecting participants. Pretested structured interviewer administered questionnaire was prepared in English and translated to local language. Findings a total of 280 lymphedema patients were involved in this study. More than half 153 (54.6%) had poor practice towards foot care practice with 95% CI (48.7, 60.4%). Patients who fetched 50 l of water or below and wore shoes at the age above 20 years were negatively associated with foot care practice, (AOR = 0.383, 95%CI: 0.155, 0.945) and (AOR = 0.261, 95%CI: 0.107, 0.63), respectively. Patients who owned only one pair and two pairs were negatively associated with foot care practice (AOR = 0.04, 95%CI: 0.009, 0.182) and (AOR = 0.27, 95%CI: 0.087, 0.85), respectively. On the other hand, attending LMMDP service and frequency of adenolymphangitis once and twice or more per month were positively associated with foot care practice (AOR = 3.339, 95%CI: 1.53, 7.285) and (AOR = 8.15, 95% CI: 3.157, 21.058) and (AOR = 9.35, 95% CI: 3.118, 28.059), respectively. Conclusion this study indicated foot care practice among lymphedema patients in Boreda district was poor. Number of litre of water collected per day, age at which footwear first worn, number of shoes owned, attending LMMDP and frequency of adenolymphangitis were significantly associated with foot care practice. Standard foot care practice should be emphasized to control progression of lymphedema. Foot care practices like skin care, exercise and elevation, washing legs, bandaging and massaging are important factors that influence in reduction of lymphedema volume and acute attacks among people who are suffering from the diseases.